Pengaruh Pemberian Reward Terhadap Motivasi Dan Hasil Belajar Siswa Kelas I Sekolah Dasar Tamalanrea IV Kota Makassar - Sriani, Sriani; Hamsiah, Andi Hamsiah; Safira, Ifa (Jounal of Primary Education, 2026)
Penelitian ini bertujuan untuk mengetahui pengaruh pemberian reward terhadap motivasi belajar siswa kelas I Sekolah Dasar Tamalanrea IV Kota Makassar, pengaruh pemberian reward terhadap hasil belajar siswa kelas I Sekolah Dasar Tamalanrea IV Kota Makassar, apakah terdapat pengaruh motivasi dan hasil belajar siswa yang signifikan antara kelas yang menerapkan pemberian reward dan kelas yang tidak menerapkan pemberian reward pada siswa kelas I Sekolah Dasar Tamalanrea IV Kota Makassar. Penelitian yang penulis lakukan bersifat deskriptif kuantitatif. Teknik pengumpulan data menggunakan metode angket, dan dokumentasi. Sedangkan teknik analisis data menggunakan perhitungan atau chikuadrat Hitung dengan tabel Product Moment. Hasil penelitian menunjukan bahwa 1) pemberian reward memiliki pengaruh yang signifikan terhadap motivasi belajar siswa kelas I SD Tamalanrea IV Kota Makassar dengan nilai thitung sebesar 6,130 lebih besar dari ttabel sebesar 1,671, dengan nilai signifikansi 0,000 yang lebih kecil dari a = 0,05. 2) pemberian reward memiliki pengaruh positif terhadap peningkatan hasil belajar siswa kelas I SD Tamalanrea IV Kota Makassar dengan hasil uji t menunjukkan nilai thitung sebesar 5,120, lebih besar dari ttabel 1,671, dengan signifikansi 0,000, yang lebih kecil dari a = 0,05. 3) pemberian reward secara signifikan meningkatkan motivasi dan hasil belajar siswa pada kelas eksperimen (kelas I-A) dibandingkan dengan kelas kontrol (kelas I-B). This study aims to determine the effect of giving rewards on the learning motivation of first grade students of Tamalanrea IV Elementary School, Makassar City, the effect of giving rewards on the learning outcomes of first grade students of Tamalanrea IV Elementary School, Makassar City, whether there is a significant influence of motivation and learning outcomes of students between classes that implement reward giving and classes that do not implement reward giving in first grade students of Tamalanrea IV Elementary School, Makassar City. The research conducted by the author is descriptive quantitative. Data collection techniques use questionnaire methods, and documentation. While the data analysis technique uses calculations or chi-square Calculation with the Product Moment table. The results of the study showed that 1) the provision of rewards has a significant effect on the learning motivation of class I students of Tamalanrea IV Elementary School, Makassar City with a t-test value of 6.130 greater than the t-table of 1.671, with a significance value of 0.000 which is smaller than a = 0.05. 2) the provision of rewards has a positive effect on improving the learning outcomes of class I students of Tamalanrea IV Elementary School, Makassar City with the results of the t-test showing a t-test value of 5.120, greater than the t-table of 1.671, with a significance value of 0.000, which is smaller than a = 0.05. 3) the provision of rewards significantly increases the motivation and learning outcomes of students in the experimental class (class I-A) compared to the control class (class I-B)..